2021
DOI: 10.24953/turkjped.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance status and outcomes in children, adolescents, and young adults: a systematic review and meta-analysis

Abstract: Background. The impacts of health insurance status on survival outcomes in children, adolescents, and young adults (aged 0-39 years) with malignant tumors have not been addressed in depth. The present study aimed to identify significant relationships of health insurance condition with overall survival or all-cause mortality among children (age 0-14 years) and adolescents and young adults (AYAs, age 15-39 years) with malignant tumors.Methods. PubMed, Wiley Cochrane Central Register of Controlled Trials, Econlit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This study indicated that the in‐hospital mortality rate during hospitalisation in the insured group was significantly lower than that in the uninsured group, regardless of PSM. Similarly, the findings of our study were also consistent with well‐known insurance disparities in cancer treatment: the lack of insurance is related to all‐cause mortality of adults with cancers 21–24 . The main reason was healthcare availability, which may result in late diagnosis, low reception of therapy, and limited accessibility of information and support services to patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study indicated that the in‐hospital mortality rate during hospitalisation in the insured group was significantly lower than that in the uninsured group, regardless of PSM. Similarly, the findings of our study were also consistent with well‐known insurance disparities in cancer treatment: the lack of insurance is related to all‐cause mortality of adults with cancers 21–24 . The main reason was healthcare availability, which may result in late diagnosis, low reception of therapy, and limited accessibility of information and support services to patients.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the findings of our study were also consistent with well-known insurance disparities in cancer treatment: the lack of insurance is related to all-cause mortality of adults with cancers. [21][22][23][24] The main reason was healthcare availability, which may result in late diagnosis, low reception of therapy, and limited accessibility of information and support services to patients. | 1399…”
Section: Outcomes Before and After Psmmentioning
confidence: 99%